PELATIHAN PENGOPERASIAN DAN PERAWATAN MESIN PRODUKSI DENGAN KENDALI ELEKTRONIKA UNTUK PENGAJAR PROGRAM STUDI TEKNIK LISTRIK INDUSTRI DI SMK TUREN – KAB. MALANG - Mochammad Mieftah; Awan Setiawan; Rachamad.S; M.Manaf; Anang Dasa Novfowan (Jurnal Pengabdian Polinema Kepada Masyarakat, 2020)
Training on Operation and Maintenance of Production Machines with Electronic Control for Instructors in the Industrial Electrical Engineering Study Program at SMK Turen - Kab. Malang, provides additional teaching and motivation for teachers of Electrical Engineering study programs at SMK Turen practicing Operation and Maintenance of Production Machines with Electronic Control. Besides that, it can also increase additional skills for teachers of the electrical engineering study program at the current Turen Vocational School